(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper focuses on explaining how AI has been integrated into different HR functions and their impact on organizations, employees and the environment. By "machine learning" (ML) we mean a series of adaptable algorithms and learn from data to make better and better solutions to a function, usually predictions. In the business world, machine learning or AI applications are the most common is concerned with surveillance, where a data scientist creates machine learning algorithms, determines the most appropriate metrics for assessing employee performance, and trains algorithms using a sample dataset.